The tadpole of the hylodid frog Hylodes ornatus (Bokermann, 1967), including chondrocranium description, and advertisement call - Bilate, Marcos; Nogueira-Costa, Paulo; Weber, Luiz Norberto (Zootaxa, 2012)
The genus Hylodes Fitzinger is composed of diurnal frogs that live associated to lotic streams in forests (Lingnau et al. 2008; Silva & Benmaman 2008). In Brazil, this genus occurs from the states of Espírito Santo to Rio Grande do Sul (Lingnau et al. 2008; Frost 2011). Hylodes currently comprises 24 species (Frost 2011) distributed in four species groups (Heyer 1982): glaber; lateristrigatus; mertensi; and nasus. Hylodes ornatus (Bokermann) are included in “Hylodes lateristrigatus” species group with other 17 species (Silva & Benmaman 2008; Canedo & Pombal 2007). Fourteen out of 24 species of Hylodes have their larvae described (Pirani et al. 2011).